Mortality in sickle cell anemia in Africa: a prospective cohort study in Tanzania. - Julie Makani; Sharon E Cox; Deogratius Soka; Albert N Komba; Julie Oruo; Hadija Mwamtemi; Pius Magesa; Stella Rwezaula; Elineema Meda; Josephine Mgaya; Brett Lowe; David Muturi; et al. (PLoS ONE)
Background The World Health Organization has declared Sickle Cell Anemia (SCA) a public health priority. There are 300,000 births/year, over 75% in Africa, with estimates suggesting that 6 million Africans will be living with SCA if average survival reaches half the African norm. Countries such as United States of America and United Kingdom have reduced SCA mortality from 3 to 0.13 per 100 person years of observation (PYO), with interventions such as newborn screening, prevention of infections and comprehensive care, but implementation of interventions in African countries has been hindered by lack of locally appropriate information. The objective of this study was to determine the incidence and factors associated with death from SCA in Dar-es-Salaam. Methods and findings A hospital-based cohort study was conducted, with prospective surveillance of 1,725 SCA patients recruited from 2004 to 2009, with 209 (12%) lost to follow up, while 86 died. The mortality rate was 1.9 (95%CI 1.5, 2.9) per 100 PYO, highest under 5-years old [7.3 (4.8-11.0)], adjusting for dates of birth and study enrollment. Independent risk factors, at enrollment to the cohort, predicting death were low hemoglobin (<5 g/dL) [3.8 (1.8-8.2); p = 0.001] and high total bilirubin (≥102 µmol/L) [1.7 (1.0-2.9); p = 0.044] as determined by logistic regression. Conclusions Mortality in SCA in Africa is high, with the most vulnerable period being under 5-years old. This is most likely an underestimate, as this was a hospital cohort and may not have captured SCA individuals with severe disease who died in early childhood, those with mild disease who are undiagnosed or do not utilize services at health facilities. Prompt and effective treatment for anemia in SCA is recommended as it is likely to improve survival. Further research is required to determine the etiology, pathophysiology and the most appropriate strategies for management of anemia in SCA.